Gastric Electrical Stimulation for Abdominal Pain in Patients with Symptoms of Gastroparesis. Issue 5 (May 2013) - Lahr, Christopher J.; Griffith, James; Subramony, Charu; Halley, Lindsey; Adams, Kristen; Paine, Elizabeth R.; Schmieg, Robert; Islam, Saleem; Salameh, Jay; Spree, Danielle; Kothari, Truptesh; Kedar, Archana; et al.
Abdominal pain physiology may be better understood studying electrophysiology, histology, and symptom scores in patients with the symptoms of gastroparesis (Gp) treated with gastric electrical stimulation (GES). Ninety-five Gp patients' symptoms were recorded at baseline and during temporary and permanent GES. Gastric-emptying times and cutaneous, mucosal, and serosal electrogastrograms were obtained. S100-stained, full-thickness gastric biopsies were compared with autopsy controls. Sixty-eight patients reported severe pain at baseline. Severe pain patients' mean pain scores decreased with temporary GES from 3.62 to 1.29 ( P < 0.001) and nonsevere pain from 1.26 to 0.67 ( P = 0.01). With permanent GES, severe mean pain scores fell to 2.30 ( P < 0.001); nonsevere pain changed to 1.60 ( P = 0.221). Mean follow-up was 275 days. Mean cutaneous, mucosal, and serosal frequencies and frequency-to-amplitude ratios were markedly higher than literature controls. For patients with Gp overall and subdivided by etiology and severity of pain, S-100 neuronal fibers were significantly reduced in both muscularis propria layers. GES improved severe pain associated with symptoms of Gp. This severe pain is associated with abnormal electrogastrographic activity and loss of S100 neuronal fibers in the stomach's inner and outer muscularis propria and, therefore, could be the result of gastric neuropathy.